Research Progress on Immunological Biochips Based on Surface Plasmon Resonance - Mengyao Wang; Yangming Hu; Wenjun Zhang; Tianzhu Zhang; Xiaobo He (Photonics)
Biomolecular detection plays essential and irreplaceable roles in safeguarding human health, impeding the transmission of diseases, and augmenting the efficacy of treatments. The precise and specific identification of biomarkers holds profound significance for the early diagnosis, real-time surveillance, and targeted treatment of various diseases. In the initial phases of numerous diseases, the absence of distinct biomarkers in the bloodstream often leads to weak detection signals when using traditional immune detection methods such as enzyme-linked immunosorbent assays (ELISAs), chemiluminescence, and fluorescence chromatography. With the surge in research on surface plasmons, innovative approaches have recently emerged that combine surface plasmon resonance (SPR) with immunological detection techniques, reducing the detection sensitivity to 283 ag/mL, shrinking the sensor size to 2.228 µm2, and shortening the detection time to 5.5 min. This review provides an overview of the theoretical foundations of surface plasmon resonance and immunoassays and then delves into the latest advancements in biosensors based on these principles, categorizing them according to their detection mechanisms and methodologies. Finally, we discuss future research directions, opportunities, and the challenges hindering the development of highly sensitive immuno-biochips.